2004
DOI: 10.1530/rep.1.00072
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of glucocorticoids in testicular involution after active immunization of boars against GnRH

Abstract: Active GnRH immunization of boars inhibits LH and testicular steroids but the consequences for spermatogenesis are unknown. Six boars were immunized three times against GnRH at 20, 24 and 28 weeks. Another six boars served as controls. Plasma LH and FSH were determined at 28 and 31 weeks. Testosterone and cortisol were determined before killing the pigs at 32 weeks. Tissue samples were taken for histology and fluid from the seminiferous tubuli for steroid determination. Individual germ cells were counted in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 64 publications
3
29
3
Order By: Relevance
“…In the pig, an effect of cortisol on testicular steroidogenesis was not substantiated so far and the GR does not occur in Leydig cells (Wagner and Claus, 2004). However, we demonstrated GR expression in spermatogonia of boar testes which is linked with a considerable degree of apoptosis limiting overall sperm yield.…”
Section: Page 3 Of 28contrasting
confidence: 53%
See 1 more Smart Citation
“…In the pig, an effect of cortisol on testicular steroidogenesis was not substantiated so far and the GR does not occur in Leydig cells (Wagner and Claus, 2004). However, we demonstrated GR expression in spermatogonia of boar testes which is linked with a considerable degree of apoptosis limiting overall sperm yield.…”
Section: Page 3 Of 28contrasting
confidence: 53%
“…However, we demonstrated GR expression in spermatogonia of boar testes which is linked with a considerable degree of apoptosis limiting overall sperm yield. Moreover, inhibition of LH and thus testicular steroid formation by active immunization against GnRH led to an increased expression of GR by spermatogonia and thus an increase of apoptosis (Wagner and Claus, 2004). By determination of 11ß-HSD enzyme activity we could demonstrate the presence of high amounts of 11ß-HSD2 activity but not of 11ß-HSD1 activity in the testes of boars.…”
Section: Page 3 Of 28mentioning
confidence: 82%
“…In addition, seminiferous tubule diameter was reduced by 30%. Mitosis was reduced, but except for type A spermatogonia, the spermatogenic cells were reduced by about 60% (Wagner and Claus, 2004).…”
Section: 6mentioning
confidence: 91%
“…It was shown that the second dose of vaccine leads to maximal GnRH antibody titre and the concurrent drop of LH within one week . Surprisingly, FSH is not altered by vaccination of boars (Awoniyi et al, 1988a and1988b;Wagner and Claus, 2004) and it was concluded that it is regulated either by a separate releasing hormone, or by the hypothalamic secretion of activin (Padmanabhan and McNeilly, 2001).…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation